APPLICATION OF REWARDS AND PUNISHMENTS IN IMPROVING LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION IN STATE MIDDLE SCHOOL 1 TEMBILAHAN - Azwardi Azwardi (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The implementation of rewards and punishments in Islamic religious education subjects at SMA Negeri 1 Tembilahan has not been done well, the learning achievements of Islamic religious education have not shown optimal results. Therefore, this research examines the application of reward and punishment to improve the learning outcomes of PAI students in Tembilahan 1 High School. This study focuses on the forms of reward and punishment, and their application as well as improving the achievement of students' learning in Islamic religious education after the implementation of reward and punishment. This research uses a descriptive qualitative approach. In obtaining data researchers used interview, observation, and documentation methods. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data uses the researcher's diligence and triangulation of data sources. The research stages in this study include the pre-field stage, the stage of field work, the stage of data analysis and the stage of report writing. The results of this study concluded that: 1) the form of awards given to give awards to students who excel in academics and non-academics. Prizes are given in the form of compliments, body movements (giving a thumbs up), applause, daily values, smiles, writing names on the board, and adding their names. On the other hand, the punishment given contains advice and guidance, shows a sour face, gives a loud rebuke, arranges the school room and classroom, gives additional assignments, and memorizes the surah or short verses. 2) The application of rewards and punishments has become a guide for teachers to improve and control students, to create schools that are in accordance with the conditions of learning for teaching and learning activities, to support students who are active or successful with academics and non-academics, to foster student support about seeking to become students good and quality, and to encourage students to get more achievements. Giving awards and punishment has made students more motivated to follow the learning process. 3) Furthermore, student achievement in Islamic religious education shows that students pay more attention to lessons, believe in the ability to perform tasks given by the teacher, become more satisfied in the learning process, and have been able to determine what actions should be taken.